2020
DOI: 10.3390/su13010060
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Inventory of Students Quality of Life—MIS-QOL

Abstract: An analysis of the literature on the quality of life and tools for its measurement revealed a gap in the field of research tools to study the quality of life of the so-called young adults. According to the theory of emerging adulthood, people aged 18–25 significantly differ from people of other age groups, including their self-perception. The aim of this article is to present the process of creating an inventory for multidimensional research on students’ quality of life, its structural and theoretical validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…Cho (2008)'s study showed that tourist satisfaction had a positive effect on subjective well-being and psychological well-being. In addition, as in previous studies [7,60], tourist satisfaction was found to have a positive effect on the quality of life. That supports the result of this study.…”
Section: Discussionsupporting
confidence: 83%
“…Cho (2008)'s study showed that tourist satisfaction had a positive effect on subjective well-being and psychological well-being. In addition, as in previous studies [7,60], tourist satisfaction was found to have a positive effect on the quality of life. That supports the result of this study.…”
Section: Discussionsupporting
confidence: 83%
“…The period of emerging adulthood enables youngsters to discover and choose the best way to grow when in adult age. This does not exclude the importance of the changes that take place in human development at subsequent stages [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related to the other items used in our questionnaire: family, friends and university, the importance of the MIS-QOL instrument, defined by Szydło et al (2021), should be highlighted. This study shows a new and broad approach, defining a whole set of constructs that measure the student's quality of life.…”
Section: Measuring Happinessmentioning
confidence: 99%
“…-The Multidimensional Inventory of Students Quality of Life (MIS-QOL) (Szydło et al, 2021) consists of 15 dimensions and 100 items scored using a 7-point Likert-type scale, from totally disagree (1) to totally agree (7). In the study by Szydło, the MIS-QOL had a Cronbach's alpha of 0.819, 0.873 and 0.706 respectively for the selected dimensions.…”
Section: Instrumentsmentioning
confidence: 99%